Feminization of the clergy in America : occupational and organizational perspectives - Nesbitt, Paula D., 1948- (OUP E-Books., 1997)
Recent years have seen the entry of large numbers of women into the ordained clergy of Protestant churches. Nesbitt here analyzes the extent to which the large-scale entry of women into the ministry has affected the occupation.